Carrying Capacity for Extensive Fishing Based on Chlorophyll-a in The Tuok Tonga Lake, Buluh Cina Village, Siak Hulu Sub District, Kampar District, Riau Province - Yeni Handayani; Madju Siagian; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractCarrying capacity is defined as the ability of aquatic environment to support the life of organism in that area. A study aimed to assess the aquatic carrying capacity based on chlorophyll-a for extensive fishing in the Tuok Tonga Lake, Buluh China Village,Siak Hulu Sub District, Kampar District, Riau Province.The carrying capacity was determined based on primary productivity using chlorophyll-a concentration, which is indicating the existence of phytoplankton in the water. This research was conducted in June-July 2019. There were 3 stations, namely Station 1 (inlet area), Station 2 (in the middle of the lake) and Station 3 (in the end of the lake). In each stations, there were two sampling point, in the surface and in 2 Secchi depth. Sampling was done three times once/week. Water quality parameters measured were chlorophyll-a, temperature, transparency, depth, pH, dissolve oxygen, CO2, nitrate and phosphate. Results shown that chlorophyll-a: 14.03-17.07 μg/L, transparency: 61.7-62.3 cm, temperature: 29.3-31oC, depth: 125-284 cm, pH: 5, dissolved oxygen:  3.37-4.94mg/L, CO2:5.32-11.98mg/L, nitrate: 0.02-0.08 mg/L and phosphate: 0.04-0.1mg/L. Based on concentration of chlorophyll-a indicates that the carrying capacity of the Tuok Tonga Lake for extensive fishing was 0.85 tons/year.Keywords: Oxbow lake, Primary productivity, Water quality